Ornamental plant Pachystachys lutea as a source of promising endophytes for plant growth and phytoprotective activity (Acta Scientiarum. Biological Sciences, 2021)
Endophytes are growth-promoting agents capable of synthesizing phytohormones, uptaking nutrients, and controlling pathogens. There is a strong potential to exploit them in the agriculture field like biofertilizers and biocontrol agents. In this work, we aimed to evaluate endophytic fungi isolated from Pachystachys lutea for their potential to solubilize phosphate, synthesise indole acetic acid (IAA), antagonize phytopathogens, and promote plant growth under greenhouse conditions. The phosphate solubilization efficiency was assessed on Pikovskaya’s agar medium. For analysis of IAA production, mycelia plugs of endophytes were cultured in Potato Dextrose Broth medium supplemented with L-tryptophan, with Salkowski Reagent, and the absorbance of the culture was measured. The antagonism evaluation of strain Alternaria sp. PL75 against phytopathogens was performed using the paired-culture technique. The promotion of plant growth provided by Alternaria sp. PL75 was evaluated in tomato plants. All strains evaluated were able to solubilize phosphate; however, the strain Alternaria sp. PL75 was the most effective (4.29). Two strains, Nemania sp. PL27 and Alternaria sp. PL75, produced 1.86 and 1.73 Î¼g mL-1 of IAA, respectively. In the antagonism assay, the endophyte Alternaria sp. PL75 and its fungal extract showed the best results against the pathogen Moniliophthora perniciosa. The greenhouse experiment result showed the endophyte Alternaria sp. PL75 increased the plantlets emergency speed index and the percentage of germination from 60 to 81.63%. It was also observed a statistical significance in the shoot length of the treated plants with the endophyte suspension (55.38 cm) compared to the control (41.67 cm).